Mixing alcohol and energy drinks: associations with risk-taking, alcohol consumption and motivations in a New Zealand sample. (3rd March 2020) - Newcombe, David; Knaebe, Brenna; Malloy, Reuben; Peacock, Amy; Bruno, Raimondo
ABSTRACT: Background: Mixing alcohol with energy drinks (AmED use) has been purported to increase risky behavior and alcohol consumption. The current study applied a within-subject retrospective self-report design to examine the association between AmED use (versus alcohol-only) and risky behavior, alcohol consumption and motivations. Method: New Zealand alcohol consumers aged 18–35 years (n = 289; AmED users: n = 143) completed an online survey. Results: Compared to alcohol-only, AmED use was associated with significant reductions in nine of twenty-six risk taking behaviors. The average amount of alcohol consumed did not differ between sessions. Maximum alcohol intake was greater in alcohol-only sessions than in AmED sessions. Motivations for consuming AmEDs and beliefs on their effects were not related to differences in typical alcohol intake in either session. The motivation to drink AmED "for the thrill" was associated with a higher general risk-taking propensity score, but not motivations and beliefs relating to being in control and feeling less drunk. AmED users did not have a significantly higher general risk-taking propensity than non-users. Conclusions: AmED use does not appear to increase risk-taking behavior or alcohol consumption and is associated with decreased risk-taking behavior and binge drinking.